'Anything We Do, We Have to Include the Communities': Law Enforcement Rangers' Attitudes Towards and Experiences of Community–Ranger Relations in Wildlife Protected Areas in Uganda. (12th March 2016) - Moreto, William D.; Brunson, Rod K.; Braga, Anthony A.
Abstract: Wildlife crime and wildlife law enforcement have become important areas of study for criminologists. Little is known, however, of the experiences of law enforcement personnel, including their attitudes towards local villagers. Similar to previous policing research underscoring the value of understanding the perspectives of front-line law enforcement, this qualitative study examines the attitudes and experiences of law enforcement rangers towards residents living near a protected area (PA) in Uganda. Drawn from semi-structured interviews and participant observation, our findings reveal a multifaceted relationship between rangers and villagers. Despite offering mixed reactions about local residents, respondents recognized the importance of strengthening community–ranger relations. Implications for the development of co-production between rangers and villagers in the management and monitoring of PAs are discussed.